The research of social and clinico-dynamic factors of predisposition to development of depressive symptoms in patients with paranoid schizophrenia - Живаго, Христина Сергіївна (ScienceRise: Medical Science, 2016)
Background. The raise of the quality of diagnostics of depressive symptomatology in patients with paranoid schizophrenia by revelation of the factors of predisposition to its development. Materials and methods. 82 хворих patients (studied group) were examined for paranoid schizophrenia with depressive syndrome and 47 – without the syndrome of depression (group of comparison). For this aim the clinical-anamnestic, socio-demographic, clinico-psychopathological and pathopsychological methods of research were used. The scales PANSS, CDSS, HARS, HDRS, questionnaire for the assessment of social functioning and the life quality of psychic patients were also used. On the base of received results the prognostic importance of the separate factors of predisposition to the development of depressive symptomatology in patients with paranoid schizophrenia was assessed. Results of research. Social predisposing factors: absence of own family; inability to use the existent educational and professional potential; absence of work and short employment history. The age and gender belonging had not essential influence on the development of depressive symptomatology. The clinico-dynamic factors of predisposition were determined as: depressive-paranoid syndrome in the period of exacerbation; duration of exacerbation period more than 40 days; development of depressive symptomatology at the beginning of disease and its further conservation; raise of the frequency of rehospitalizations with the course of disease; short dose of supporting therapy and short-term remissions without rehabilitation support; continuous-progredient course of disease with development of apathetic-abulic defect. Conclusions. Depressive symptomatology can develop at any stage of schizophrenia disease. Being associated with depressive symptomatology, disease fast acquires the unfavorable, malignant course with reduction of the quality and duration of emissions and raise of rehospitalization level already in first 5 years of disease. It is proved by the low level of compliance, development of hospitalism, decrease of social functioning and level of life quality. The revealed social and clinico-dynamic predisposition factors will allow raise the level of diagnostics of depressive symptomatology in patients with paranoid schizophrenia. Elaboration of the complex socio-medical rehabilitation of patients with depressive symptomatology at paranoid schizophrenia that takes into account the revealed factors of predisposition will favor the increase of the level of social functioning and life quality of this contingent of patients